H.E.S.S. II - Telescope structure, reflector and drive system - Deil, C.; van Eldik, Christopher; Förster, A.; Hermann, G.; Hofmann, W.; Panter, M. (4th International Meeting on High Energy Gamma-Ray Astronomy, 2009)
The currently operating phase I of the imaging atmospheric Cherenkov telescope array H.E.S.S. consists of four telescopes, each with a 107 m reflector, which are arranged on the corners of a square of 120 m side length. At the moment, the collaboration is building a much larger 600 m telescope in the center of the array. This will not only increase the sensitivity in the currently accessible energy regime, but will in addition lower the energy threshold of the system. The H.E.S.S. II telescope will have a parabolic reflector of 36 m focal length consisting of 850 individual mirrors, which can be automatically aligned, similar to the H.E.S.S. I telescopes. The drive system will have a repositioning speed of 100 deg/min in elevation and 200 deg/min in azimuth and achieve an online tracking accuracy of - 1 arcmin and an offline absolute pointing accuracy of - 10 arcsec. This proceeding contribution presents details on the technical implementation of the telescope mechanics, optics and drive system. © 2009 American Institute of Physics.
Keywords: Cherenkov telescope; H.E.S.S.